Measures for screening for intimate partner violence: a systematic review. Issue 3 (31st March 2016) - Arkins, B.; Begley, C.; Higgins, A.
Accessible summary: What is known on the subject?: Intimate partner violence (IPV) has a significant impact on the onset, duration and recurrence of mental health problems. Prevalence rates of IPV are significantly higher in mental health services, but the studies are limited. Accurate assessment of IPV is important for decision making in risk assessment and safety planning within mental health nursing. Psychometrically tested tools are the most accurate way to identifying all areas of IPV abuse: physical, sexual and psychological. What this paper adds to existing knowledge?: Ten IPV screening tools were identified in healthcare and three tools; Women Abuse Screen Tool (WAST), Abuse Assessment Screen (AAS) and Humiliation, Afraid, Rape and Kick (HARK) were identified as having strong psychometric values as they assessed all areas of IPV and were validated against an appropriate reference standard. None of the three IPV tools identified (WAST, AAS, HARK) were tested on men or in mental health settings impacting the gender sensitivities of the tools and the reliability of the prevalence rates of IPV in mental healthcare. Over seventy percent of the studies reviewed were conducted in America this impacts the cultural sensitivities of the IPV tools. What are the implications for practice?: IPV screening needs to be incorporated as a priority in mental health services in order to reduce the morbidity and mortality issues associated with this abuse. Psychometric tools to screen for IPV need to be incorporated to assist mental health professionals in decision making in risk assessment and safety planning. Further research is needed to improve the psychometric properties of IPV tools in mental health settings, to ensure they are culturally and gender sensitive. Abstract: Objective: Intimate partner violence (IPV) is a public health priority due to the physical and mental impacts it has on health. No existing reviews have focused on the psychometric properties of IPV screening tools used to screen men and women within a mental health context. This review aimed to identify the best psychometrically tested screening tools available to assess all areas of IPV in men and women in mental health setting. Method: Databases psycArticles, PsycINFO, Social Science, CINAHL, PubMed and Cochrane were searched from their starting date through to July 2015. Eligible studies were published in peer‐reviewed publications in English. Results: Thirty‐six studies met the inclusion criteria. Ten IPV screening tools were identified. Three tools assessed all areas of IPV and were validated against an appropriate reference standard. One study tested IPV screening tool in a mental health setting. Conclusion: Mental health nurses need to incorporate a psychometrically tested IPV tool as part of risk assessment and safety planning for clients. This review identified three tools that are suitable for identifying IPV in a mental health context. However, further research is necessary to validate IPV screening tools that are culturally sensitive and have been validated with men and women.